Rejection and victimization among first graders primary school with education support needs - Monjas, María I.; Martín-Antón, Luis J.; García-Bacete, Francisco-Juan; Sanchiz, María L. (Anales de Psicología / Annals of Psychology, 2014)
This study aims to analyze the social rejection and victimization experienced by students with educational support needs compared to their peers. Participants were 1351 first graders primary school, 253 of them (18.7%) were labeled by their teachers as students with educational support needs since they had difficulties which required special and additional educational support. The information has been provided by peers (sociometric typology, social reputation and sociometric rating), teachers (social competence) and the students themselves (victimization and self-competence). The results indicate that students with educational support needs are more rejected, have worse social reputation (more aggressive, more isolated and less prosocial) and their teachers consider they are less competent socially. These students report that they are victimized more often than their peers and they perceive themselves as less competent cognitively and less accepted by their peers. This shows a clear characterization of these students as rejected and excluded. Moreover, the aspects that characterize the profile of rejection are amplified when applied to these students, which highlights the necessity of paying special and careful attention to this group of risk.